Ultrasonographic measurement of liver, portal vein, hepatic vein and perivisceral adipose tissue in high-yielding dairy cows with fatty liver during the transition period. Issue 4 (8th November 2018) - Fiore, Enrico; Perillo, Laura; Morgante, Massimo; Giudice, Elisabetta; Contiero, Barbara; Curone, Giulio; Manuali, Elisabetta; Pavone, Silvia; Piccione, Giuseppe; Gianesella, Matteo
Abstract : The aim of the present study was to evaluate the potential for diagnosis of fatty liver by means of ultrasonographic measurement of liver and perivisceral adipose tissue as an alternative to blood indicators of lipomobilization and liver biopsy in periparturient high-yielding dairy cows. Thirty cows were enrolled and divided into two groups. The evaluation of body condition score (BCS), non-esterified fatty acids (NEFA), β-hydroxybutyrate (BHB), liver and perivisceral adipose tissue ultrasonographic measurement and histological liver lipid content (GdL) was performed at 15 ± 5 d prepartum ( T 0 ), 10 ± 2 d postpartum ( T 1 ), 30 ± 2 d postpartum ( T 2 ) and 50 ± 2 d postpartum ( T 3 ). Mesenteric fat thickness (the thickness of the perivascular adipose tissue) measured on ultrasound was shown to be an independent determinant of fatty liver. The cut-off of the ultrasonographic evaluation of the liver may be useful as a first and practical approach in identifying fatty liver. In conclusion, a non-invasive and reliable diagnostic method for predicting the risk of fatty liver in high yielding dairy cows has been demonstrated.